USING PPP (PRESENTATION, PRACTICE AND PRODUCTION) STRATEGY ON SPEAKING ACHIEVEMENT: STRATEGY ON SPEAKING ACHIEVEMENT - Darmawan Budiyanto (Universitas Muhammadiyah Muara Bungo, 2019)
This study aimed to find out whether or not there was any significant differences in speaking achievement in Recount Text between students who were taught by using PPP (Presentation, Practice and Production) Strategy and those who were not. There were 66 students of eighth grade students of SMP Negeri 2 Palembang that was involved in this study as the sample. They were divided into two groups, experimental group consisted of 33 students and control group consisted of 33 students. For the sample, the writer chose class of VIII 7 as control group and class of VIII 6 as experimental group. The method of this study was used quantitative method with quasi experimental design. The experimental group was taught by using PPP (Presentation, Practice and Production) Strategy meanwhile the control group were taught by using Discussion Strategy. The result showed that the mean score of experimental group increased from 68.182 in pretest to 81.515 in posttest. Furthermore, the result of independent t-test from experimental and control group shown that the t-obtained was 2.346 and it was higher than t-table 1.669. In conclusion, that there was a significant difference between students who were taught using PPP (Presentation, Practice and Production) strategy and students who were not.